2010
DOI: 10.1021/cb9002738
|View full text |Cite
|
Sign up to set email alerts
|

Cross Species Quorum Quenching Using a Native AI-2 Processing Enzyme

Abstract: Bacterial quorum sensing (QS) is a cell-cell communication process, mediated by signaling molecules, that alters various phenotypes including pathogenicity. Methods to interrupt these communication networks are being pursued as next generation antimicrobials. We present a technique for interrupting communication among bacteria that exploits their native and highly specific machinery for processing the signaling molecules themselves. Specifically, our approach is to bring native intracellular signal processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 42 publications
0
82
0
1
Order By: Relevance
“…Interestingly, AI-2 responses of V. harveyi cultures were also inhibited by LsrKtreated AI-2, despite the fact that AI-2 signaling proceeds through extracellular detection via a membrane-bound sensor kinase in this species. Additionally, exogenously added LsrK blocked quorum sensing under coculture conditions (84), suggesting that LsrK could be useful for quenching both intraspecies and interspecies quorum sensing.…”
Section: Enzymatic Inactivation Of Non-ahl Qs Signalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, AI-2 responses of V. harveyi cultures were also inhibited by LsrKtreated AI-2, despite the fact that AI-2 signaling proceeds through extracellular detection via a membrane-bound sensor kinase in this species. Additionally, exogenously added LsrK blocked quorum sensing under coculture conditions (84), suggesting that LsrK could be useful for quenching both intraspecies and interspecies quorum sensing.…”
Section: Enzymatic Inactivation Of Non-ahl Qs Signalsmentioning
confidence: 98%
“…LsrK is the cytoplasmic enzyme responsible for phosphorylation of AI-2 following import into the cell (108). Roy et al found that by providing LsrK exogenously to E. coli or S. Typhimurium cultures, they could inhibit QS activation by blocking AI-2 import (the negative charge of phospho-AI-2 prevents its transport via the Lsr transporter) (84). Interestingly, AI-2 responses of V. harveyi cultures were also inhibited by LsrKtreated AI-2, despite the fact that AI-2 signaling proceeds through extracellular detection via a membrane-bound sensor kinase in this species.…”
Section: Enzymatic Inactivation Of Non-ahl Qs Signalsmentioning
confidence: 99%
“…In contrast, the Lsr system and LsrG in particular targets the interspecies signal AI-2. This is the only natural system known so far to degrade AI-2 signal, and there are already multiple studies showing that the Lsr system can function as an AI-2 quenching system (11,43). Our work shows that interference with LsrG alters the function of Lsr, suggesting that it could be a useful target for AI-2-based quorum-quenching therapies.…”
Section: Discussionmentioning
confidence: 62%
“…P-DPD is the intracellular inducer of the lsr operon, the gene products of which form a system capable of terminating AI-2-mediated bacterial behaviors (11,43). Using NMR, x-ray crystallography, and a combination of in vitro and in vivo assays, we showed that LsrG catalyzes the isomerization of P-DPD to P-TPO (and its non-hydrated form, P-HPD).…”
Section: Discussionmentioning
confidence: 99%
“…54 Involvement of keto intermediates as chemically and kinetically competent substrates was further proved by the synthesis of 2 and 3-keto intermediates, 3 and 5 and testing against LuxS, 54,56 The importance of QS inhibition in regulating bacterial pathogenicity and other community related behaviors can be further underscored by the natural evolution of bacterial quorum quenching enzymes to prevent these population based activities of bacteria competing for energy and nutrients. 67,68 (1) inhibition of synthesis of autoinducer molecules, (2) inhibition of binding of autoinducer to sensor proteins, (3) inhibition of molecular targets downstream of autoinducer synthesis, (4) sequestration of autoinducer via molecular traps, 61 (5) degradation of autoinducer, [67][68][69] and (6) inhibition of autoinducer transport and release. 6 General strategies for manipulation of QS include:…”
mentioning
confidence: 99%